The Analysis of Vitamin C Content in Facial Serum Using UV–Vis Spectrophotometric Method - Susanti Kamau; Abdon Saiya; Vlagia Paat (Jurnal Kimia Fullerene, 2026)
Facial serum is a category of skin care products designed to deliver concentrated active ingredients that promote the penetration of bioactive compounds into deeper layers of the skin, targeting various skin problems such as aging, hyperpigmentation, and acne. According to the literature, stable formulations of vitamin C at the right concentration can significantly reduce signs of aging and improve skin radiance. This study aims to determine the concentration of vitamin C contained in commercially available facial serums claimed to contain vitamin C, using the UV-Visible spectrophotometry method. Three samples were analyzed, namely; Serum 1, Serum 2, and Serum 3. A calibration curve was obtained using standard series concentrations of 2 ppm, 4 ppm, 6 ppm, and 8 ppm at an optimum wavelength of 241.50 nm, resulting in a regression equation of y = 0.0242x + 0.3022 with a correlation coefficient of r = 0.9975 and a determination coefficient of R² = 0.9950. The limit of detection (LOD) was 0.54 ppm and the limit of quantification (LOQ) was 1.81 ppm. The results of this study indicate that all tested samples contained vitamin C, with concentrations in Serum 1 = 338 mg/L, Serum 2 = 267.7 mg/L, and Serum 3 = 284.2 mg/L